Investigation of Photosensitive Polyimide With Low Coefficient of Thermal Expansion and Excellent Adhesion Strength for Advanced Packaging Applications - Yuan-Chiu Huang; Han-Wen Hu; Yun-Hsi Liu; Hui-Ching Hsieh; Kuan-Neng Chen (IEEE Journal of the Electron Devices Society, 2024)
In advanced packaging schemes, such as fan-out integration technology, photosensitive polyimide (PSPI) is the key material to the fabrication of panel level redistribution-layer (RDL). However, a large mismatch of coefficient of thermal expansion (CTE) between silicon (Si) and PSPI will cause serious warpage issue. Furthermore, polyimide deformation may occur under external heat and pressure, leading to deterioration of RDL reliability. In this work, PSPI with low CTE and excellent adhesion strength on different substrate was developed and evaluated by lithography test, adhesion test, and reliability test, showing the high feasibility for the application in advanced packaging process.